Bioassay-Guided Isolation, and Identification of Bioactive Compounds from Garcinia Atroviridis (Asam Gelugor) - Mohamed Mackeen, Muhammad Mukram (1998)

(untitled)
This study was undertaken to characterise the biological activities of Garcinia atroviridis, a food plant and traditional vegetable, as well as to isolate and identify its bioactive constituents Ethnobotanical reports on the use of G atroviridis as an anti-infective agent and biopreservative, coupled with the paucity of scientific reports on the biological activities of G atroviridis were the basis for selecting this plant as the subject of this study Crude extracts (methanol dimethyl sulfmade-91) of various parts of this plant were screened for antimicrobial (disc diffusion method), Cytotoxic (microtitration method), brine shrimp toxic, antitumour-promoting (Epstem Barr Virus activation assay) and antioxidant (ferric thiocyanate and thiobarbitunc assays) activities. The crude extracts exhibited predominantly antibacterial activity with the roots showing the strongest inhibition against the test bacteria at the minimum inhibitory dose (MID) of 156µg/disc. Although all the extracts failed to inhibit the growth of most of the test fungi, significant antifungal activity against Cladosporium herbarum was exhibited by most notably the fruit extract (MID 100 µg), and the leaf extract (MID 400 µg) None of the extracts were Significantly cytotoxic and lethal towards brine shrimps. The root, leaf, trunk and stem bark extracts (except for the fruits) showed strong antioxidant activity exceeding that of the standard antioxidant, α-tocopherol. Antitumour promoting activity (> 95% inhibition) was shown by the fruit, leaf, stem and trunk bark extracts.